The The Impact of Working Environment on Employee Loyalties with Job Satisfaction as an Intervening Variable - Nadhila Alifi Andarsari; Pompong B. Setiadi (Ilomata International Journal of Management, 2023)
In this dynamic era, maintaining loyal and qualified human resources is a step to increase company productivity in order to achieve set goals. Many factors affect employee satisfaction, one of which is job satisfaction. Maintaining employee loyalty by increasing the level of job satisfaction is done by creating a conducive and positive work environment. The work environment includes the physical environment, psychological environment, and social environment. This study aims to determine the effect of the work environment on employee loyalty with job satisfaction as an intervening variable. The method used in this research is review with 20 articles. Based on the results of this study, the work environment has a strong influence on employee job satisfaction. A work environment that can make employees develop optimally with appropriate rewards can increase worker satisfaction. Employee satisfaction is very influential in increasing employee loyalty to the company. Employees with high levels of satisfaction will give their energy and time for the success of the organization.